Arsenic induces gender difference of estrogen receptor in AECII cells from ICR fetal mice. (April 2019) - Che, Wangjun; Yang, Mengping; Cheng, Yaling; Wu, Mei; Lan, Yajia; Zhang, Hao
Abstract: Arsenic is a confirmed human lung carcinogen with estrogenic activity. There are gender differences in the incidence of lung cancer. Estrogen receptors (ER) play an important role in the process of the development of lung cancer. In order to understand the gender difference effects of ER during carcinogenesis of lung induced by arsenic, the effects of arsenic and estrogen receptor antagonist (ICI182780) on expression levels of estrogen receptor beta (ERβ), extracellular regulated protein kinase (ERK1/2) and nuclear factor κB (NF-κB/P65) in type II alveolar epithelial cells (AECII) from different sex ICR fetal mice lung were detected. Results showed that arsenic increased the expression levels of mRNA and protein of ERβ, ERK1/2 and NF-κB/P65, and ICI182780 inhibited the increase. Furthermore, there remains a gender difference in these changes. To summarize, the observations here strongly suggested that estrogen receptor and its mediated signal pathway molecules might have critical roles of the gender difference of incidence of lung cancer in arsenic induced. Highlights: Arsenic induced gender differences of estrogen receptor and its mediated signal pathway in AECII cells from ICR fetal mouse. The expression of estrogen receptor beta induced by arsenic could be inhibited by estrogen receptor antagonist (ICI 182780). AECII cells from male and female ICR fetal mouse was used in this study, respectively.